Dose and duration of opioid use in patients with cancer and noncancer pain at an outpatient hospital setting in Malaysia - Zin, Che Suraya; Ab Rahman, Norny Syafinaz; Ismail, Che R.; Leong, W. Choy, (Wiley-Blackwell Publishing Ltd, 2016)
Background: There is currently limited data available on the patterns of opioid prescribing in Malaysia. This study investigated the patterns of opioid prescribing and characterized the dosing and duration of opioid use in patients with noncancer and cancer pain. Method: This retrospective cross sectional study was conducted at an outpatient hospital setting in Malaysia. All prescriptions for opioids (dihydrocodeine, fentanyl, morphine and oxycodone) issued between January 2013 and December 2014 were examined. The number of prescriptions and patients, the distribution of mean daily dose, annual total days covered with opioids, and annual total opioid dose at the individual level were calculated and stratified by noncancer and cancer groups. Results: A total of 1015 opioid prescriptions were prescribed for 347 patients from 2013 to 2014. Approximately 41.5% of patients (n=144/347) and 58.5% (n=203/347) were associated with noncancer and cancer diagnosis respectively. Oxycodone (38.0%) was the highest prescribed primarily for the noncancer group. Majority of patients in both noncancer (74.3%) and cancer (60.4%) groups were receiving mean daily doses of <50 mg morphine equivalents. The chronic use of opioid (>90 days per year) was associated with 21.8% of patients in the noncancer group and 17.5% in the cancer group. Conclusions: